The Hague Peace Conference of 1907: a Retrospective after 110 Years - S. I. Chernyavskiy (Tractus Aevorum, 2017)
One hundred and ten years ago the Second Peace Conference was held in The Hague. It adopted important documents which codified some laws and customs of war thus contributing to the foundation of the system of international humanitarian law. This Conference was a logical continuation of the 1899 Peace Conference, convened at the initiative of Russia, which established general rules for the peaceful settlement of conflicts between states, as well as a number of resolutions and declarations regarding the conduct of military operations. The article analyzes the reasons for convening these international fora and their significance for the world community.